Marie Curie Alumni Association - Cyprus Chapter - (:unkn) unknown (My University, 2026)
The group has been created to bring closer all the Marie Curie fellows and Alumni that live in the geographical area of Cyprus under a common goal, to enhance the image of the MCAA within the Cypriot territory.